Shame on you! The antecedents of sickness remote work attendance behaviors - Ferreira, A.I.; Mach, M.; António Cunha Meneses Abrantes (85th Annual Meeting of the Academy of Management, 2025)
The rise of remote working practices has given way to new phenomena, such as coworker remote work exemplification–efforts to be perceived as hardworking, committed, or capable of working additional hours remotely–, and gossip. These behaviors can be explained by the emotions of shame they evoke, which may be linked to remote work presenteeism. Drawing from social information processing and appraisal theory of emotion, we hypothesize that remote work exemplification and negative workplace gossip have a positive indirect effect on remote work presenteeism through the emotion of shame. The results of a three-wave data collection research design with a sample of 246 participants support the hypotheses that coworker remote work exemplification and workplace negative gossip have a positive indirect effect on remote work presenteeism through shame. This study provides important theoretical